2023
DOI: 10.1007/s13201-023-01941-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SEBS and SEBAL algorithms for estimating wheat evapotranspiration (case study: central areas of Khuzestan province)

Abstract: This study aimed to accurately estimate daily wheat evapotranspiration using two remote sensing algorithms, Surface Energy Balance System (SEBS) and Surface Energy Balance Algorithm for Land (SEBAL), in central Khuzestan province during 2019–2020. The results of two algorithms were compared with lysimeter (as a direct method), FAO-Penman–Monteith (FAO-PM), two temperature-based methods (Hargreaves-Samani and Blaney-Criddle), two radiation-based methods (Priestley–Taylor and Doorenbos–Pruitt), and two mass tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One of the latest studies compared the SEBS and SEBAL algorithms for estimating daily wheat evapotranspiration in central Khuzestan province. Both algorithms showed high compatibility with lysimeter data, outperforming other methods and suggesting their suitability for accurate evapotranspiration estimation in the region [119]. In another study [120], under the arid and semi-arid environment of the Northern part of Saudi Arabia, the SEBAL and METRIC models were compared for estimating ET.SEBAL was deemed superior in estimating ET compared to METRIC.…”
Section: Intercomparison Of Et Estimation Among the Temperature-based...mentioning
confidence: 97%
“…One of the latest studies compared the SEBS and SEBAL algorithms for estimating daily wheat evapotranspiration in central Khuzestan province. Both algorithms showed high compatibility with lysimeter data, outperforming other methods and suggesting their suitability for accurate evapotranspiration estimation in the region [119]. In another study [120], under the arid and semi-arid environment of the Northern part of Saudi Arabia, the SEBAL and METRIC models were compared for estimating ET.SEBAL was deemed superior in estimating ET compared to METRIC.…”
Section: Intercomparison Of Et Estimation Among the Temperature-based...mentioning
confidence: 97%
“…A study by Sun et al (2019) evaluated four SEB models (SEBAL, SEBS, S-SEBI, and SSEB) in China using Landsat 8 images, concluding that SEBAL performed the best, while SEBS and SEBI underestimated ET. Meanwhile, Zoratipour et al (2023) reported that both SEBAL and SEBS algorithms were highly compatible with lysimeter measurements in central Khuzestan province. Therefore, it is an ongoing research topic to assess the efficiency of RSbased ET monitoring methods.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, several strategies have been proposed for validating actual ET products obtained from satellite data. In general, these validations are carried out using field data from weighing lysimeters [30][31][32][33], as well as flux tower data [34][35][36], which are the main and most widely distributed databases of local measurements. Remote sensing methods represent a valuable tool for ET monitoring as they allow us to map the patterns of this hydrological variable at different spatial scales.…”
Section: Introductionmentioning
confidence: 99%